The axisymmetric stress analysis of double contact problem for functionally graded materials layer with arbitrary graded materials properties. (1st October 2016) - Liu, Tie-Jun; Zhang, Chuanzeng; Wang, Yue-Sheng; Xing, Yong-Ming
Abstract: In this paper, the axisymmetric double contact problems for a functionally graded layer indented by a rigid cylindrical indenter and a rigid spherical indenter are considered. A linear multi-layered model is applied to model the functionally graded layer whose shear modulus varies as an arbitrary function. The Hankel integral transform technique and the transfer matrix method are applied to convert the double contact problem to a system of coupled singular integral equations which are solved by the numerical method. The numerical results show that the stiffness ratio and the gradient index have great effect on the contact region and the contact pressure.